Mengembangkan Digital Marketing dalam Penjualan Toko Batu Bata Merah Mas Andi di Desa Bengle - Raharjo, Gunawan; Huda, Muhammad Nurul; Meyfadil, Diky (Jurnal Pelayanan dan Pengabdian Masyarakat (Pamas), 2026)
Mas Andi Red Brick Store in Bengle Village faces marketing challenges due to its continued reliance on conventional methods such as direct promotion and face-to-face sales. This strategy is considered less effective in today’s digital era, where consumers are more active in using online platforms to search for information and make purchases. To address this issue, a Community Service Program (PKM) was carried out with the aim of helping the business partner develop their enterprise through the implementation of digital marketing strategies to increase sales.The PKM activities were conducted in several stages, including initial observation, website usage training, intensive mentoring, and direct implementation of digital strategies. The training materials included the creation of social media accounts such as Instagram and Facebook, the development of promotional content, and the management of digital interactions with consumers. This was done because many potential customers search for red brick products via social media platforms.The results of this activity show that the business partner has started to understand the importance of digital marketing. The partner is now able to independently create and upload promotional content and expand their market reach through digital means. This activity not only improved their technical skills but also encouraged a change in mindset regarding the consistent use of digital technology to build a business image.The close collaboration between the service team and the partner created a participatory and practical learning environment. It is hoped that the skills gained can continue to be developed, allowing the partner’s business to grow and compete in an increasingly digital marketplace